Holistic Employee Welfare through Maqasid al-Shariah: Rethinking HRM in Islamic Legal Framework (LexIslamica: A Multidisciplinary Approach to Islamic Law and its Contemporary Applications, 2025)
Human Resource Management (HRM) plays a crucial role in the sustainability and success of organizations, especially in an increasingly competitive economic context. This study examines the application of the principles of Maqasid As-Syariah in HRM, which not only focuses on economic aspects but also on the holistic well-being of employees, encompassing psychological, social, and spiritual dimensions. By emphasizing the values of justice, trustworthiness, and welfare, this approach aims to create a fair and harmonious work environment. The study finds that the implementation of Maqasid As-Syariah principles can enhance job satisfaction, loyalty, and employee productivity through fair policies in compensation, skill development, and support for employees' social and spiritual lives. Despite challenges in its implementation, such as social inequality and a lack of understanding of Sharia values, the integration of these principles into company policies is expected to contribute to employee well-being and organizational sustainability. This research provides recommendations to raise awareness and understanding of the importance of applying Maqasid As-Syariah in HRM, enabling companies to create a more productive work environment and contribute to the development of a more prosperous society.